The Impact of Effectiveness of Zakat Management and Transparency of the Use of Zakat Funds on Improving Welfare and Community Empowerment in Central Java - Mokodenseho, Sabil; Imban, Yuniarti; Dilapanga, Sarini; Manggo, Tetriana; Paputungan, Aisa; Kobandaha, Serli; Modeong, Nazria; Paputungan, Prayascita (Westscience Press, 2024)
This research investigates the impact of Zakat management effectiveness and transparency of fund utilization on welfare improvement and community empowerment in Central Java, Indonesia. A quantitative approach, utilizing Structural Equation Modeling with Partial Least Squares analysis, was employed to analyze data collected from 135 respondents, including Zakat beneficiaries and stakeholders. The results indicate significant positive relationships between Zakat management effectiveness, transparency of fund utilization, welfare improvement, and community empowerment. Efficient Zakat management practices and transparent fund utilization are found to positively influence welfare improvement and community empowerment, highlighting the importance of governance mechanisms and accountability in Zakat distribution. These findings have important implications for policymakers, Zakat institutions, and stakeholders involved in Zakat management, emphasizing the need for enhanced transparency and equitable distribution of Zakat funds to promote socio-economic development and empowerment in Central Java.